The effect of bivalirudin and closure device on bleeding outcomes after percutaneous coronary interventions. Issue 1 (12th August 2014) - Dobies, David R; Barber, Kimberly R; Cohoon, Amanda L
Abstract : Introduction: Studies have demonstrated bivalirudin efficacy in some patients at increased risk of bleeding. The aim of this study was to determine the extent to which bleeding reduction is achieved among all patients using bivalirudin as compared with a heparin with or without 2B3A inhibitor strategy. Methods: This is a real-world, large-scale retrospective study utilising the American College of Cardiology (ACC) data from a 37-hospital Ascension Health System. The registry represents routine clinical practice between 1 June 2009 and 30 June 2012. End points included major bleeding, major adverse cardiac events and death. Multivariate regression analysis modelled on predictors of end points. Results: This study included 58 862 PCI procedures. Major bleeding rates were lowest for bivalirudin plus closure device overall (OR=0.53, CI 0.21 to 0.84, p=0.001). The use of a device for access closure contributed to the greatest declines in major bleeding. Compared with heparin with device, bivalirudin with device had a significantly lower rate of bleeding (OR=0.37, CI 0.18 to 0.74, p=0.005). The use of device had a greater effect on decreasing bleeding among patients receiving bivalirudin compared with heparin, especially among women (p=0.001). After adjustment for 2B3A use, this advantage was no longer significant in ST segment elevation myocardial infarction patients (OR=1.8, CI 0.5 to 6.0, p=0.34). Conclusions: All risk groups in this real world database representing current clinical practice benefited from the use of bivalirudin and device closure with lower risk groups benefiting the most. This robust analysis of real-world clinical data supports a combined treatment strategy of bivalirudin and closure device.